The Geography of Place in the Qur’anic Narrative: A Hermeneutical Study of the Story of Moses and Al-Khidr through the Lenses of Philosophical Symbolism and Pedagogical Perception - Alriteemi, Abraheem; Mowafg Masuwd; Masoud, Mohieddin; Alsayd, Abdulnasir; Aboujanah, Yousuf; Alrumayh, Safa; Ayad, Nahid (Tebuireng: Journal of Islamic Studies and Society, 2025)
This study offers an interpretive, semantic, and educational analysis of the story of Moses and al-Khidr in Surah al-Kahf (verses 60–82). It focuses on the symbolic and geographical dimensions of place and its role in shaping the educational and epistemological experience of Prophet Moses (peace be upon him). The research adopts an integrative approach that combines classical Qur’anic exegesis, Islamic mysticism, and theories of symbolic space in religious and philosophical thought. The story is analyzed as a sequence of transitional phases in a geographical space that goes beyond physical description, carrying spiritual and pedagogical implications. These stages include the symbolic starting point at the "junction of the two seas," the loss of the fish, the meeting with al-Khidr, and the three events (the scuttling of the ship, the killing of the boy, and the building of the wall). The research shows how Qur’anic geography transforms into a multi-layered semantic space, where each place represents a stage in Moses’ inner transformation, from acquired knowledge to divinely inspired knowledge, and from the logic of appearance to the insight of the unseen. The study reveals that the setting in this story is not merely a background for events, but rather an active educational element that contributes to shaping major concepts such as knowledge, submission, spiritual excellence (ihsan), and epistemic humility. The research concludes that Qur’anic pedagogy is deeply intertwined with its symbolic and emotional contexts and relies on them to form the ideal human being.